2019
DOI: 10.1007/s40820-019-0337-2
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Nanostructured Waste Copper Wires for High-Energy Alkaline Battery

Abstract: HIGHLIGHTS • Electronic waste Cu wires were successfully used as a cost-effective current collector for high-energy wire-type rechargeable alkaline batteries. • The scalable approach was applied to reduce, reuse, and recycle electronic waste. • A developed wire-type rechargeable alkaline battery exhibited a high-energy-density of 82.42 Wh kg −1 with long-term cycling stability. ABSTRACT Rechargeable alkaline batteries (RABs) have received remarkable attention in the past decade for their high energy, low cost,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 608 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The four-electron ORR mechanism in an alkaline environment is generally as follows: , (1) O 2 (g) + * + H 2 O (l) + e – → OOH* + OH – ; (2) OOH* + e – → O* + OH – ; (3) O* + H 2 O (l) + e – → OH* + OH – ; and (4) OH* + e – → * + OH – . The asterisk (*) indicates the active center on the surface of the catalyst; O*, OH*, and OOH* are intermediates that are adsorbed during the electrochemical reaction. , According to the Sabatier principle, the best catalyst at the apex of the volcano should not be too strong or too weak to bond the reaction intermediates . Studies have found that the ORR behavior of the catalyst can be significantly improved by optimizing the morphological structure, surface structure, electronic structure, and nanostructure strategies of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The four-electron ORR mechanism in an alkaline environment is generally as follows: , (1) O 2 (g) + * + H 2 O (l) + e – → OOH* + OH – ; (2) OOH* + e – → O* + OH – ; (3) O* + H 2 O (l) + e – → OH* + OH – ; and (4) OH* + e – → * + OH – . The asterisk (*) indicates the active center on the surface of the catalyst; O*, OH*, and OOH* are intermediates that are adsorbed during the electrochemical reaction. , According to the Sabatier principle, the best catalyst at the apex of the volcano should not be too strong or too weak to bond the reaction intermediates . Studies have found that the ORR behavior of the catalyst can be significantly improved by optimizing the morphological structure, surface structure, electronic structure, and nanostructure strategies of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The four-electron ORR mechanism in an alkaline environment is generally as follows: 11,12 the catalyst; O*, OH*, and OOH* are intermediates that are adsorbed during the electrochemical reaction. 11,12 According to the Sabatier principle, the best catalyst at the apex of the volcano should not be too strong or too weak to bond the reaction intermediates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, radiation-stimulated immune responses have shown limited efficacy, particularly when tumors exhibit low X-ray absorption and energy deposition capacities [ 342 , 343 ]. Disjoint oxygen supply and demand within tumors result in hypoxic areas with high levels of hydrogen peroxide, which induce adaptive antioxidant mechanisms [ 344 , 345 ]. Subsequently, high concentrations of reducing substances, such as glutathione, quench •OH generated by RT, ultimately reducing its efficacy [ 346 ].…”
Section: Cancer Radiation Therapymentioning
confidence: 99%
“…The work function is an electronic property typically considered for the characterization of layered heterostructures [6], field emission devices [7] and energy conversion and storage devices [8,9]. Similarly, the difference in work function between one metal and one semiconductor is used to explain the basic characteristics of heterojunctions and the formation or absence of potential barriers and depletion regions that describe the formation of Schottky or ohmic contacts (figure 2).…”
Section: Introductionmentioning
confidence: 99%